O movimento e o imutável: a memória da arte em Sans Soleil - Costa Júnior, Edson Pereira da (2013)
The research focus on the film-essay Sans Soleil (1982, Sunless), directed by the french filmmaker Chris Marker. It aims to study the possibilities of audiovisual format which mediates the relationship between the subject and the different manifestations of the past. In order to accomplish this objective, this paper analyses two aspects of the film: the formal and the thematic. On the first, the emphasis is about the essayistic structure and Intertextuality levels. On the second, we ponder on historical and spiritual conceptions that compose the narrative. Throughout the study, we keep a constant dialogue with other Marker‟s productions and artists that influenced him, like Alfred Hitchcock and Andrei Tarkovski.